سيميائية العنوان في قصص الأطفال: نماذج قصصية جزائرية مختارة - سحنون, نورة; شفيري, فتيحة (جامعة الوادي - university of Eloued, 2022)
أصبح العنوان في المنجز القصصي للصغار بعد خوض القصّاصين غمار الكتابة التعليمية والترفيهية يفرض سلطته على المتلقّي بوصفه علامة تجارية تغري نحو القراءة وتجذب المتلقّي لِاقتناء القصة. وهذا لا يتحقق إلاّ بنسج خطاب العنوان تركيبا ودلالة ومجازا حتى يحرّض القارئ على فكّ شفراته وفتح مغاليقه. ولعل الكُتّاب الجزائريين على غرار "مها المنشور"، "نادية يحياوي"، "أبو العيد دودو" يُدركون أهمية العنوان في إنتاج الدلالة ويقرّون أنّ عنوان القصة يأخذ مساحة من الإبداع والفنية. وللوقوف على الخصائص السيميائية للعنوان، عالج المقال بالوصف والتحليل نماذج مختارة من عناوين قصص الطفل ومنها؛ تين هنان، الشليا تاج الأوراس، الاِنتظار، حيث توصلت الباحثتان إلى أنّ اِختيار مؤلفي هذه القصص لعناوينها جاء وفق خصائص سيميائية وفنّية، وهذا يدلّ أنّ للعنوان والعنونة حُظوة لدى منتجي أدب الطفل، كما أنّهم يوظفونه توظيفا مغريا ودقيقا. Abstract: The title has become in the story production for children, after the storytellers entered into the educational and entertainment writing, imposing its authority on the receiver as a brand that tempts towards reading and attracts the receiver to acquire the story. This can only be achieved by adjusting the title’s discourse in structure, significance and metaphor, in order to incite the reader to decode it and open its locks. Perhaps Algerian writers such as "Maha El Manshor", "Nadia Yahyaoui", "Abu El-Eid Doudou" realize the importance of the title in the production of semantics and acknowledge that the title of the story takes a space of creativity and artistry. In order to identify the semiotic characteristics of the title, the article deals selected samples of the titles of children's stories with description and analysis, including; Tin Hanan, Al-Shelia Taj Al-Auras, The Waiting. The researchers concluded that the authors of these stories have chosen their titles according to semiotic and artistic characteristics. This indicates that the title and titrology are favored by producers of children's literature, and they employ it in an attractive and accurate way.
مقال
Keywords: طفل؛ قصص الأطفال؛ عنوان؛ سيمائية؛ متلقي; child; stories for kids; Title; semiotics